MAJOR DEPRESSIVE DISORDER: AN ALARMING STIGMA OF PREGNANT WOMEN - Khan, Muhammad Junaid; Hamza, Muhammad Asim; Sarwar, Iram; Rashid, Muhammad Adnan (Journal of Ayub Medical College Abbottabad, 2020)
Background: Major depressive disorder is the most common psychiatric disease affecting women. Pregnancy significantly increases its prevalence, especially in developing countries. Antenatal major depression is an alarming condition for the mother and the growing fetus. This study aimed to find the frequency of antenatal depression and its relation with obstetric predictors. Methods: This cross-sectional study was conducted during Jan-March of 2014, in Benazir Bhutto women and children, Hospital, Abbottabad. By non- probability consecutive sampling techniques, total 96 pregnant women in third trimester were included during outpatient visiting hours. After inclusion and exclusion criteria, they were diagnosed for low back pain and major depressive disorder. All the data and questions were recorded in a pre-tested questionnaire. Verbal informed consents were obtained. SPSS software (version 21) was used for statistical analysis. Results: The sample included 96 participants with a mean age of 24.56±4.24 years, and mean duration of pregnancy 35.06±3.80 weeks. Forty-one women (42.7%) had high school education level, women from urban areas were 50 (52.1), 54 (56.3%) were from age group, 21-25 years, and 54 (56.3%) had first pregnancy. Among the total, 68 (70.8%) were depressed and 42 (43.8%) were of mild severity. Two third, i.e., 66 (68.8%) had low back pain. None of the results were statistically significant. Conclusion: Major depressive disorder (of mild severity) are quite high in 3rd-trimester pregnant population of Abbottabad. Frequency was more in uneducated younger age group women, resident of remote areas with first conception were more depressed. Keywords: Major Depressive Disorder; Pregnant Women; Foetus; Developing countries